Gastrointestinal complications of HIV infection: changing priorities in the HAART era. Issue 6 (18th January 2008) - Wilcox, C M; Saag, M S
Abstract : It has now been some 25 years since the initial description of AIDS. Following these observations, the epidemiology, natural history and manifestations of this disease have been well characterised. Intense investigation has better characterised HIV, resulting in the development of effective drug therapies to arrest disease progression. These multidrug combinations, termed highly active antiretroviral therapy or HAART, can suppress the viral load to the undetectable range and secondarily halt the destruction of CD4 T lymphocytes. This virological response is associated with a marked improvement in survival and absence of the many complications related to immunodeficiency. For patients who respond to HAART, the current emphasis is on treating side effects from the medications as well as treating other non-AIDS-related disorders. However, given the cost and complexities of these regimens, there are many patients who continue to present with the classic manifestations of AIDS, and, especially in the developing world, we will continue to see these patients for years to come.